Learning by heart - Barth, Roland S. (San Francisco : Jossey Bass, 2001)
This title seeks to show how to accomplish the most difficult task in any school reform - changing a school's culture so that the people living and working in that culture are no longer afraid to take a risk.
Keywords: Education -- Aims and objectives -- United States; Educational change -- United States; Effective teaching -- United States; Group work in education -- United States; Learning